2013
DOI: 10.1136/bmjopen-2013-002645
|View full text |Cite
|
Sign up to set email alerts
|

Individual-level, network-level and city-level factors associated with HIV prevalence among people who inject drugs in eight Russian cities: a cross-sectional study

Abstract: ObjectivesTo ascertain HIV prevalence among people who inject drug (injection drug users (IDUs)) in the Russian Federation and identify explanations for the disparity in different cities.DesignCross-sectional survey with serological testing for HIV and hepatitis C virus prevalent infections.Setting8 Russian cities—Irkutsk, Omsk, Chelyabinsk, Yekaterinburg, Naberezhnye Chelny, Voronezh, Orel and St Petersburg.ParticipantsIn 2007–2009 active IDUs were recruited by respondent-driven sampling with a target sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 39 publications
1
44
1
2
Order By: Relevance
“…We started with the hypothesis that HCV prevalence levels and factors associated with higher prevalence would be similar to our previously published findings for HIV-1 [13]. Our analysis showed that HCV seroprevalence was associated with HIV-1 seroprevalence at both the individual and city level.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…We started with the hypothesis that HCV prevalence levels and factors associated with higher prevalence would be similar to our previously published findings for HIV-1 [13]. Our analysis showed that HCV seroprevalence was associated with HIV-1 seroprevalence at both the individual and city level.…”
Section: Discussionsupporting
confidence: 56%
“…Five have populations of more than one million inhabitants; the others have between 350,000 and 700,000 inhabitants. Observations from previous studies [14-17] and from our analysis of the distribution of HIV-1 among the PWID recruited as part of this study together suggest that individual risks, social networks, and city-to-city differences in drug markets all have influenced the epidemic situation of HIV among Russian PWID populations [13]. Observations also suggest that the same individual-, network-, and city-level factors might have influenced the spread of HCV and contributed to variations in HCV prevalence.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Acute HIV-1 infection is associated with a high viral load and thus an increased likelihood of transmission. It is known that within the network PWID in St. Petersburg do share syringes and injection paraphernalia frequently, 15,24,25 allowing the infection of the PWID network members to occur very rapidly after HIV-1 acquisition and viral load spike of a single member of this network. The homogeneous acute infection as a source of the epidemic may explain the low diversity of the virus circulating in the population.…”
Section: Discussionmentioning
confidence: 99%
“…11 The HIV prevalence among PWID increased linearly from 2% in 1998 to 30% in 2003, and reached 59% in the most recent studies. [12][13][14][15][16] Respondentdriven sampling (RDS), a chain referral sampling method commonly used to reach hidden populations, has become the most popular method to recruit samples of PWID and MSM in Russia. 17,18 These populations have been studied separately; however, little is known about crossover between these groups.…”
mentioning
confidence: 99%